2013
DOI: 10.3390/catal3040914
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Liquid Solution of Chitosan as Organocatalyst

Abstract: Chitosan, which is derived from the biopolymer chitin, can be readily dissolved in different ionic liquids. The resulting homogeneous solutions were applied in an asymmetric Aldol reaction. Depending on the type of ionic liquid used, high asymmetric inductions were found. The influence of different additives was also studied. The best results were obtained in [BMIM][Br] without an additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The result suggested that cyclic amines with moderate alkalinity and two active centers exhibited high activity. Plausible pathways are shown in Scheme 2 and we consider that the ratio of the aldol condensation was promoted by the hydrogen bonding between the amino group or the hydroxy group of 3-pyrrolidinamine or 3-pyrrolidinol and the aldehyde [24,25]. …”
Section: Resultsmentioning
confidence: 99%
“…The result suggested that cyclic amines with moderate alkalinity and two active centers exhibited high activity. Plausible pathways are shown in Scheme 2 and we consider that the ratio of the aldol condensation was promoted by the hydrogen bonding between the amino group or the hydroxy group of 3-pyrrolidinamine or 3-pyrrolidinol and the aldehyde [24,25]. …”
Section: Resultsmentioning
confidence: 99%
“…It was shown (Figure 5), that while the freeze-drying method originates a porous membrane structure, oven drying produces compact films, with a smoother surface using water as an anti-solvent [78]. Additionally, deacetylation into chitosan does not occur with the use of ILs [79]. Other ILs such as choline hexanoate ([Ch][Hex]) and choline citrate ([Ch][Cit]) have also been successful in this process [80].…”
Section: Dissolutionmentioning
confidence: 99%
“…In 2013, Wilhelm and co‐workers applied homogeneous solutions of chitosan with different molecular weights (between 100k and 300k g mol −1 ) in various ionic liquids to catalyze the asymmetric aldol reaction (Scheme ) . Purified chitosan (1 g) was dissolved in ionic liquid (10 g) at 70 °C.…”
Section: Natural Polysaccharide‐based Organocatalystsmentioning
confidence: 99%
“…In 2013, Wilhelma nd co-workers appliedh omogeneous solutions of chitosan with different molecular weights (between 100k and 300k gmol À1 )i nv arious ionic liquids to catalyzet he asymmetrica ldol reaction (Scheme 6). [41] Purified chitosan (1 g) was dissolved in ionic liquid (10 g) at 70 8C. The catalytic ability of this system provedt ob ed ependent on the counteraniono f the cationic ionic liquid and on the ability of the ionic liquid to form hydrogen bonds, thus disaggregating the polymer chains.…”
Section: Aldol Reactionmentioning
confidence: 99%